IMAGE OF WOMEN IN GADIS KRETEK NOVEL BY RATIH KUMALA BASED ON FEMINISM PERSPECTIVE - Suhendra, Suhendra; Mahajani, Tri; Nurjaman, Aam; Talitha, Stella; Hilal M, Ruyatul; Lestari, Tania (UNIVERSITAS PAKUAN, 2021)
Novel is part of a literary work that contains a series of life stories of characters and people around them. The portrayal of character is described by an arranged series of events, setting, and furrows. It aims to examine a womens image in the feminism perspective of a Gadis Kretek novel. The feminism perspective in the writing is focused on the image of women embracing the physical image of a womans physical transformation. Psychic image, linked to the ability of women to think, to aspire, and to feel. Image in the family, concerning the roles of women in the family. Image in society can be demonstrated by the female role in society embodied in behavior. This research used a qualitative descriptive method with library study techniques. The conclusion of this study shows that the image of female physis is more characterized by the physical depiction of the main character from aspects of age, maturity, and behavior like adults. Psychic imagery is depicted through the permmature of thinking in a mature figure. The image in the family appears to be attached to the main character who plays a child. The image in society is characterized by the role of the main character portrayed as an intelligent, independent, responsible, and cheerful woman.